EasyContext: Facilitando o desenvolvimento de aplicações com a Awareness API - Tabosa, Davi Batista; Viana, Windson (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2018: Anais Estendidos do XXIV Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia.2018.4565, 2018)
Due to the popularity of smartphones and their built-in sensors, Context-Aware Mobile (CAM) applications are on the rise. Some libraries and APIs help developers to create CAM applications, such as the Google Awareness API. However, the initial configuration, the write of context-aware rules, and code readability persist being complex tasks, specially for beginner developers. This paper proposes an approach to ease the development of CAM applications using Awareness API. Our proposal, called EasyContext, includes a Web Configurator and an Android Framework, which hides code complexity and the Awareness API configuration. A PoC using the EasyContext is also presented.